Learning styles and academic performance of the communication area in the basic education students - Yana, Marisol (2019)
The research consisted of determining the relationship between learning styles and academic performance in the area of ​​Communication in students of the educational institution "Carlos Rubina Burgos" of Puno, 2017. It was of a basic type, with non-experimental descriptive-correlational transectional design. 63 students constituted the census sample. We used the techniques: survey and indirect systematic observation, the instrument was the Honey-Alonso Learning Styles Questionnaire (CHAEA) consisting of 80 items divided into four sections of 20 items corresponding to learning styles (active, reflective, theoretical and pragmatic) and a file to determine the level of academic performance in the area of ​​Communication. To analyze the data we used the (SPSS) version 22 and the Pearson correlation, it was determined that between the reflective learning style and the level of academic performance the correlation is moderate positive (r =, 489 **). On the other hand, the relationship between the theoretical (r =, 353 **) and pragmatic (r =, 292 *) learning styles with academic performance in the communication area is low and significant positive and in the learning style Active and academic performance there is a very low positive relationship (r = .189) and not significant. In terms of academic performance, they are at the expected level of achievement of 61.9%.